Mapping crop damage by wild boars using multi-scale risk modeling in Northeast China - Ding, N; Atzeni, L; Chen, Y; Lyu, Z; Shi, K (Wiley, 2023)
Balancing development and conservation is one of the major challenges for modern societies. Negative human–wildlife interactions, especially crop raiding by wildlife, greatly undermine this objective. Jilin Province in Northeast China encompasses ecosystems of high biodiversity value but endures serious losses in crop yields due to wild boars (Sus scrofa). Mitigation measures have been hindered by knowledge gaps in wild boar damage patterns. Our objective was to investigate how wild boar damage responded to human-dominated landscapes, evaluating landscape patterns of damage at multiple ecological scales, thus providing a provincial map of damage risk to assist with damage mitigation. We used 1,144 coordinates of wild boar damage from 2009 to 2013 to train multi-scale risk models with the maximum entropy algorithm. Damage risk was highest on gentle slopes and in heterogenous landscapes composed of fragmented plantations and cropland, with high edge density among small discontinuous patches, and with dense settlements in countryside areas with sporadic road networks. Scale had a substantial effect on relationships between damage and landscapes. We recommend mitigating the conflict risk by improving the compensation system and reducing the damage frequency through repelling, electric fencing, and dissuasive feeding.